2020
DOI: 10.1080/18366503.2020.1834060
|View full text |Cite
|
Sign up to set email alerts
|

Application of geoeconomics in seaport operations: a theoretical proposal for post Covid-19 recovery strategy

Abstract: Johor Port and Port of Tanjung Pelepas (PTP) are two adjacent seaports act as backbone of the Malaysian international trade and economy. The probability of these seaports catering the same client is very high and may cause overlapping in the hinterland area. This will further result in the waste of resources, congestion in traffic and reducing the competitiveness of seaports. The situation worsened during Covid-19 outbreak as these two seaports faced issues related to capacity and efficiency. This paper employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Our research study has also confirmed the impact of the COVID-19 pandemic on changes in handling the seaport hinterland transport [48]. Additionally, we found that the problems encountered by road transport operators at border crossings during the pandemic as well as decreased passenger traffic in the railway infrastructure increased the attractiveness of rail transport on the routes to/from the hinterland.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our research study has also confirmed the impact of the COVID-19 pandemic on changes in handling the seaport hinterland transport [48]. Additionally, we found that the problems encountered by road transport operators at border crossings during the pandemic as well as decreased passenger traffic in the railway infrastructure increased the attractiveness of rail transport on the routes to/from the hinterland.…”
Section: Discussionsupporting
confidence: 80%
“…Depellegrin et al [47] indicated a negative impact of progressive lockdown restrictions connected with the COVID-19 pandemic on the ship traffic frequency and cargo handling at ports. Jeevan et al [48] identified a negative impact of the COVID-19 pandemic which deepened the problems faced by seaports as a result of overlapping in the hinterland area. Van den Oord et al [49] analysed the influence of the pandemic on the management of seaports as organizational networks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The main problem currently faced by the seaport is its very competitive environment (Jeevan et al, 2020). The seaport faces difficult times because of its former monopolistic market captive position.…”
Section: Importance Of Marketing In Freight Nodesmentioning
confidence: 99%